Recent advancements in encapsulation of bioactive compounds as a promising technique for meat preservation. (November 2021) - Smaoui, Slim; Ben Hlima, Hajer; Ben Braïek, Olfa; Ennouri, Karim; Mellouli, Lotfi; Mousavi Khaneghah, Amin
Abstract: Encapsulation is currently considered as one the most valuable methods for preserving aromatic compounds or hiding odors, enhancing their thermal and oxidative stability, and expanding their food applications. Indeed, this current article was aimed to provide an overview regarding the encapsulation of plant bioactive compounds and the spray-drying and extrusion processes with a focused discussion regarding the encountered challenges for meat and meat product preservation. Furthermore, different ranges of carbohydrates as wall materials (carriers) besides the process conditions' effects on the encapsulation effectiveness and the particle size of the encapsulated bioactive compounds have been discussed. The encapsulation of these compounds ameliorates the quality of the stored meat products by further delaying in microflora growth and lipid/protein oxidation. Therefore, the innovative technologies for plant active compounds encapsulation offer a prospective alternative for natural preservation development in the meat industry. Graphical abstract: Unlabelled Image Highlights: Bioactive compounds from plant materials can be used as encapsulating agents. Spray-drying and extrusion are effective and scalable encapsulation techniques. Microencapsulation preserves bioactive compounds. Microencapsulated natural antioxidants can enhance meat products quality.